Safety distance for pressure‐resistance tests of cylindrical pressure vessels in the industrial field. Issue 8 (2nd May 2022) - Shin, Seolin; Kim, Eui Soo; Kang, Chankyu; Jung, Seungho
Abstract: The number of pressure vessel bursts (PVBs) has reduced since the 1990s due to the introduction of many rules and regulations. However, accidents frequently occur during pressure resistance tests (pneumatics) and there are scant safety guidelines for examining pressure vessels. Thus, this study proposes a safe distance to prevent accidents during a test, based on the explosion energy and vessel shape. First, the maximum explosion energy was computed using Brode's equation and the distance and overpressure were nondimensionalized via Sachs' scaling. Next, the overpressure ratio of the spherical tank (opsphere ) was calculated based on the overpressure ratio of the cylindrical tank (opcylinder ), considering the length to diameter ratio of the cylindrical vessel. Finally, the function of the safety distance was obtained. The result was validated by comparing it with data from the catastrophic failure that occurred at D. D. Williamson & Co. Inc. in 2003. This study could help establish safety guidelines and the prevention of PVB damage. Abstract : Proposed methodology to calculate the safety distance for pressure vessel burst.